2015
DOI: 10.1248/bpb.b15-00306
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effects of γ-Tocotrienol Are Associated with a Suppression in Aerobic Glycolysis

Abstract: Aerobic glycolysis is an established hallmark of cancer. Neoplastic cells display increased glucose consumption and a corresponding increase in lactate production compared to the normal cells. Aerobic glycolysis is regulated by the phosphatidylinositol-3-kinase (PI3K)/Akt/ mammalian target of rapamycin (mTOR) signaling pathway, as well as by oncogenic transcription factors such as c-Myc and hypoxia inducible factor 1α (HIF-1α). γ-Tocotrienol is a natural isoform within the vitamin E family of compounds that di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…This member of the vitamin E family of compounds displays potent anticancer effects at doses having little or no effect on normal cell viability [164]. To test the role of glycolysis in the effect caused by γ-tocotrienol, Parajuli et al [165] used the MCF-7 breast cancer cell line. γ-tocotrienol was found to decrease MCF-7 cell growth, coincident with a concentration-dependent decrease in glucose consumption and lactate production.…”
Section: γ-Tocotrienolmentioning
confidence: 99%
“…This member of the vitamin E family of compounds displays potent anticancer effects at doses having little or no effect on normal cell viability [164]. To test the role of glycolysis in the effect caused by γ-tocotrienol, Parajuli et al [165] used the MCF-7 breast cancer cell line. γ-tocotrienol was found to decrease MCF-7 cell growth, coincident with a concentration-dependent decrease in glucose consumption and lactate production.…”
Section: γ-Tocotrienolmentioning
confidence: 99%
“…Since γ-tocotrienol also induces a reversal of EMT in these cells and canonical Wnt and Hedgehog signaling pathways are involved in promoting EMT, it can be concluded that γ-tocotrienol inhibition of EMT is mediated by a corresponding reduction in canonical Wnt and Hedgehog signaling in malignant MDA-MB-231 human breast cancer cells. This hypothesis is further evidenced by the finding that γ-tocotrienol inhibition of Wnt and Hedgehog signaling and reversal of EMT is associated with a significant decrease in migration, invasion and stemness of these cells [12].…”
Section: Resultsmentioning
confidence: 88%
“…Studies have indicated that γ-tocotrienol induced inhibition of EGF-dependent proliferation of preneoplastic CL-S1 mouse mammary epithelial cells resulted from an inhibition of G-protein-mediated activation of adenylyl cyclase, cyclic adenosine monophosphate (cAMP) production, as well as a reduction in phosphorylated (activated) extracellular signal-regulated kinase 1/2 (ERK1 and ERK2) [33]. In addition to the inhibition of mitogenic signaling, γ-tocotrienol is known to inhibit numerous vital cellular functions including inhibition of cell cycle progression [13], mevalonate pathway [34,35], glycolysis [12], angiogenesis [36], and epithelial mesenchymal transition (EMT) [37].…”
Section: Vitamin E and Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations